Detection of Ophiocordyceps sinensis and Its Common Adulterates Using Species-Specific Primers - Liu, Yang; Wang, Xiao-yue; Gao, Zi-tong; Han, Jian-ping; Xiang, Li (Frontiers in Microbiology, 2017)
Ophiocordyceps sinensis is a fungus that infects Hepialidae caterpillars, mummifying the larvae and producing characteristic fruiting bodies (stromata) that are processed into one of the most valued traditional Chinese medicines (TCM). The product commands a very high price due to a high demand but a very limited supply. Adulteration with other fungi is a common problem and there is a need to test preparation for the presence of the correct fungus. In the current study, a PCR-based approach for the identification of O. sinensis based on a segment of the internal transcribed spacer (ITS) region was developed. The segments is 146-bp in size and is likely to be amplified even in materials where processing led to DNA fragmentation. Primer development was based on the alignment of sequence data generated from a total of 89 samples of O. sinensis and potential adulterants as well as sequences date from 41 Ophiocordyceps species and 26 Cordyceps species available in GenBank. Tests with primer pair, DCF4/DCR4, demonstrated generation of an amplicon from DNA extracted from O. sinensis stromata, but not from extracts derived from adulterants. Species-specific primer pairs were also developed and tested for detection of the common adulterants, C. gunnii, C. cicadae, C. militaris, C. liangshanensis, O. nutans. The collection of primers developed in the present study will be useful for the authentication of preparation claiming to only contain O. sinensis and for the detection of fungi used as adulterants in these preparations.